(untitled) (Medicine Today, 2013)
A prospective Hospital based study was done to find out the aetiology of neonatal hyperbilirubinaemia. One hundred cases were studied during a period from January to December 2003 on the neonatal unit of CMCH and different clinics of chittagong city. Among them 69% were male and 31% were female. Neonatal septicemia was the commonest cause of neonatal hyperbilirubinaemia found in 28% case follwed by blood group incompatibility (27%). DOI: http://dx.doi.org/10.3329/medtoday.v24i2.15011 Medicine Today 2012 Vol.24(2): 73-74